2021
DOI: 10.3389/fimmu.2021.745523
|View full text |Cite
|
Sign up to set email alerts
|

IL-40: A New B Cell-Associated Cytokine Up-Regulated in Rheumatoid Arthritis Decreases Following the Rituximab Therapy and Correlates With Disease Activity, Autoantibodies, and NETosis

Abstract: BackgroundInterleukin 40 (IL-40) is a newly identified B cell-associated cytokine implicated in humoral immune responses and B cell homeostasis. As B cells play a pivotal role in autoimmunity, we investigated the function of IL-40 in rheumatoid arthritis (RA).MethodsIL-40 expression was determined in the synovial tissue from RA and osteoarthritis (OA) patients. IL-40 was analysed in the serum/synovial fluid of patients with RA (n=50), systemic lupus erythematosus (SLE, n=69), OA (n=44), and healthy controls (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“… 23 Recently, IL-40 was found upregulated in RA, suggesting a role for this molecule in B-cell driven rheumatic diseases. 24 As found in RA synovium, IL-40 was strongly upregulated in pSS among lymphocytic infiltrates and ductal epithelial cells and significantly correlated with the FS. Specifically, epithelial cells are thought to play an important pathogenetic role in pSS, as suggested by the demonstration that, in the histopathological lesions of patients with pSS, ductal and acinar salivary gland epithelial cells display high levels of several immunoactive molecules that are known to mediate the lymphoid cell homing, antigen presentation and the amplification of epithelial cell–immune cell interactions.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“… 23 Recently, IL-40 was found upregulated in RA, suggesting a role for this molecule in B-cell driven rheumatic diseases. 24 As found in RA synovium, IL-40 was strongly upregulated in pSS among lymphocytic infiltrates and ductal epithelial cells and significantly correlated with the FS. Specifically, epithelial cells are thought to play an important pathogenetic role in pSS, as suggested by the demonstration that, in the histopathological lesions of patients with pSS, ductal and acinar salivary gland epithelial cells display high levels of several immunoactive molecules that are known to mediate the lymphoid cell homing, antigen presentation and the amplification of epithelial cell–immune cell interactions.…”
Section: Discussionmentioning
confidence: 63%
“…The first link to autoimmune disease dates back to 2012 when the presence of C17orf99 gene was described as a marker of autoimmune hepatitis 23. Recently, IL-40 was found upregulated in RA, suggesting a role for this molecule in B-cell driven rheumatic diseases 24. As found in RA synovium, IL-40 was strongly upregulated in pSS among lymphocytic infiltrates and ductal epithelial cells and significantly correlated with the FS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 10 Very recently, an upregulation of IL-40 in RA was demonstrated. 11 12 Based on our study on RA, 11 the elevation of IL-40 in RA is associated with disease activity, autoantibodies and the externalisation of neutrophil extracellular traps (NETosis). We also demonstrated that elevated serum levels of IL-40 significantly decreased following B-cell depletion therapy (rituximab) in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to our in vitro studies, IL-40 acts as an inducer of chemokines, and metalloproteinase release by RA synovial fibroblasts. 11 …”
Section: Introductionmentioning
confidence: 99%